Let's Play! Exploring the Impact of Summer Day Camp Participation on the Physical and Psychosocial Experiences of Diverse Urban Youth. - Henert, Shaine; Jacobs, Jenn; Wahl-Alexander, Zach (Child & Adolescent Social Work Journal, 2021)
This exploratory study examined the effect of participation in a 6-week physical activity-based summer day camp (Camp PAL) that incorporates life skills promoted in the Teaching Personal & Social Responsibility model (TPSR) on physical activity and psychosocial outcomes of diverse urban youth. Specifically, we assessed children's daily physical activity levels, self-perceptions of competence in their social life, physical appearance, and global self-worth, and personal and interpersonal developmental skills. In addition, observational data were collected to assess the fidelity of the Camp PAL program in delivering elements of the TPSR model. The results showed that participation in the Camp PAL program helped children achieve substantial daily physical activity levels—which frequently decrease during the summer months when children are not participating in school physical education, especially for marginalized youth. The results also showed that all campers felt their program participation benefited them in terms of their social lives, physical appearance, and global self-worth as well as their development of personal/social, goal setting, and initiative skills. Campers of color reported benefitting the most in a number of these psychosocial domains. Observational data analysis supported the effectiveness of the camp program in delivering elements of the TPSR model. The results provide initial evidence that summer camp programs, like Camp PAL, may help diverse populations of urban children maintain adequate daily physical activity levels while simultaneously promoting their broader social welfare.